Iranian cinema uncensored : contemporary film-makers since the Islamic revolution - Rahbaran, Shiva, 1970-; Mohajer, Maryam (London : I.B. Tauris, 2016)
In this unique book, twelve of the most renowned and important filmmakers of contemporary Iran speak candidly about creating cinema in a revolutionised and traumatised society. They reflect on the Iranian revolution and the influence of its aftermath on their work, as well as the effects of their work on audiences worldwide. They offer first-hand insights into the influence they have had on the making of Iran's image; how the seeds of New Iranian Cinema were sown decades before the revolution and how these seeds grew into a cinema that became a global phenomenon, despite censorship, ideology wars, sanctions and political isolation; and how they took sustenance from the works of western and global cineastes as well as from the long tradition of art and poetry of Iran.
Introduction: new Iranian cinema in its cultural, historical and political context -- 1. Mohammad Beheshti: the role of post-revolutionary institutions in the development of Iranian cinema -- 2. Bahram Beyzaie: the myth of revolutionary cinema -- 3. Abbas Kiarostami: where is the revolution? -- 4. Dariush Mehrjui: Islamic ideology and post-revolutionary intellectual films -- 5. Bahman Farmanara: exporting new Iranian cinema -- 6. Rakhshan Bani-Etemad: cinema as a mirror of the urban image -- 7. Majid Majidi : the revolution and the cleansing of film Farsi -- 8. Jafar Panahi: cinema and resistance -- 9. Tahmineh Milani: new Iranian cinema and the education of the masses -- 10. Ebrahim Hatamikia: cinema, war and peace -- 11. Mohsen Makhmalbaf: an interview that never was.
Includes bibliographical references and index.
Translated from the Persian.
Keywords: Motion picture producers and directors -- Iran -- Interviews; Motion pictures -- Iran -- History; Motion pictures -- Censorship -- Iran; Iran